STRATEGI PENGEMBANGAN UMKM OLEH DINAS KOPERASI DAN USAHA MIKRO KOTA SEMARANG - Aurora Latita Aulia Ramadhanti; Endang Larasati; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
An outbreak of the Covid-19 virus attacked the country of Indonesia. The entry of the Covid-19 virus into this country greatly affects and has an impact on all sectors in society's life, such as the MSME sector. The existence of this outbreak resulted in MSME spread across several sub-districts in the city of Semarang experiencing a decrease in turnover and experiencing problems. The problems faced by SMEs in the city of Semarang are such as capital problems, production problems, marketing problems, and other marketing. The purpose of this study is to analyze the strategy of the Cooperatives and Micro Enterprises Office of Semarang City in overcoming problems that occur in MSMEs and analyze the driving factors in planning this strategy. This study uses a qualitative method with a descriptive approach. The theory in this study uses the theory of Bryson. The results of the study show that the MSME development strategy in overcoming problems uses the SWOT method, namely 1) providing MSME product marketing facilities or facilitation, 2) Assisting in facilitating MSME product standardization, 3) Providing MSME access to sources of capital, 4) Implementing marketing digitization. In strategic planning by the Agency, there are driving factors, namely the suitability of the vision and mission of the Semarang City Cooperatives and Micro Enterprises Office, the availability of adequate facilities and infrastructure, the availability of an adequate budget, the use of information and communication technology in the MSME sector, and the involvement of stakeholders in the MSME sector.